Shoot or send to die: the truncated initiatives of the Frondicismo regarding the repression of terrorism (1960) (Quinto Sol, 2025)
This article addresses the various strategies developed during the civilian presidency of Arturo Frondizi (1958-1962) for the treatment of citizens convicted by military courts-martial for committing terrorist acts. Specifically, we will address the two main initiatives that the government attempted to promote after the public declaration of the Plan for Internal State Commotion (CONINTES) in March 1960: the implementation of the death penalty and the transfer of convicted prisoners to the Isla de los Estados (Island of the States). We affirm that the study of this process of discussion and repercussions in the press and the political arena sheds light on the conception of terrorism held at that time, as well as the positioning regarding the repression of social conflict defended by the main political groups in the early 1960s. The main sources used correspond to both documentation produced by state institutions and press materials. We also have oral testimony from former political prisoners, which is unique in shedding light on the specific experiences of those persecuted and tried by military tribunals that year.
Keywords: death penalty; prison islands; prison; terrorism